2008
DOI: 10.1021/la702392v
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of a Surfactant Boundary Lubricant Film by a Hydrophilic−Hydrophilic Diblock Copolymer

Abstract: The coadsorption from aqueous solutions of an anionic-neutral hydrophilic-hydrophilic diblock copolymer onto a mica-suported surfactant bilayer of a cationic oligomeric surfactant has been investigated. By using an atomic force microscope and a surface forces apparatus nanotribometer, we studied the resulting film morphology, the interactions between two coated surfaces, and the frictional properties of the boundary film. When the coated surfaces were compressed while being fully immersed in an aqueous surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…Drummond and co-workers have explored this in some detail, using surfactants that adsorb onto the substrate surface mixed with a diblock copolymer to modify the lubrication performance. 44,48,79,80 In their initial studies, using a double-chained surfactant which in itself provided low friction and high load bearing capacity, it was found that coadsorption of a hydrophobically end-modified poly(ethylene oxide) compromised the lubrication performance. 48 In later studies oligomeric cationic surfactants were utilized, and the layers formed by these surfactants alone had relatively low load bearing capacity.…”
Section: Load Bearing Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Drummond and co-workers have explored this in some detail, using surfactants that adsorb onto the substrate surface mixed with a diblock copolymer to modify the lubrication performance. 44,48,79,80 In their initial studies, using a double-chained surfactant which in itself provided low friction and high load bearing capacity, it was found that coadsorption of a hydrophobically end-modified poly(ethylene oxide) compromised the lubrication performance. 48 In later studies oligomeric cationic surfactants were utilized, and the layers formed by these surfactants alone had relatively low load bearing capacity.…”
Section: Load Bearing Capacitymentioning
confidence: 99%
“…However, co-adsorption of a poly(acrylic acid)-poly(acrylamide) diblock copolymer significantly enhanced the cohesion of the adsorbed layer and thus increased the load bearing capacity. 79 It was also noted that there was an optimal copolymer concentration range that should not be exceeded in order to retain the excellent lubricity. 79,80 The structure of the surfactant played an important role in the enhancement of the load bearing capacity achieved by addition of the diblock copolymer.…”
Section: Load Bearing Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the cohesion of the mix layer and its lubricant properties are dramatically improved by this coadsorption, probably because the PAA polyion interacts with several surfactant molecules creating a physical network on the substrate. We observed that the mix layers can be conditioned under shear to achieve a state of very good lubrication properties, after the incidence of one or several delamination transitions [12]. However, at high copolymer concentrations, we detected signs of mechanical weakness: the system presented a transition from a low friction force steady state to a high friction force steady state associated with the reduction of the thickness of the boundary layers [13].…”
Section: Introductionmentioning
confidence: 82%
“…In previous studies, we have reported that this copolymer coadsorbs into self-assembled layers of several cationic surfactants [12,13]. We have shown that the cohesion of the mix layer and its lubricant properties are dramatically improved by this coadsorption, probably because the PAA polyion interacts with several surfactant molecules creating a physical network on the substrate.…”
Section: Introductionmentioning
confidence: 83%